2020
DOI: 10.7150/jca.38217
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced MFAP5 Promotes Tumor Migration and Invasion via AKT Pathway in Head and Neck Squamous Cell Carcinoma

Abstract: Objective: Microfibrillar-associated protein 5 (MFAP5) is highly expressed in many types of cancers. Our previous study has observed that overexpression of MFAP5 was correlated with lymph nodes metastasis and poor prognosis in head and neck squamous cell carcinoma (HNSCC), but the underlying mechanism is poorly understood. Materials and methods: The MFAP5 expression is detected under hypoxia condition. HNSCC cell lines are transfected with MFAP5-expressing lentivirus vector to establish stable overexpression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…The Akt pathway is downstream of some of these regulators such as MFAP5, PDZK1, and CAV1, which are related to cell progression and growth. The expression of MFAP5 also affected inflammatory related genes in previous studies 31,33,35 , and its inhibition in our data by NAS suggests that MT1 may be responsible for limiting GC proliferation and growth, and at the same time preventing early luteinization at the antral follicular stage through activation of the Akt pathway.…”
Section: Effects Of Mt1 Receptor Activation or Inhibition On Human Gc...supporting
confidence: 74%
See 1 more Smart Citation
“…The Akt pathway is downstream of some of these regulators such as MFAP5, PDZK1, and CAV1, which are related to cell progression and growth. The expression of MFAP5 also affected inflammatory related genes in previous studies 31,33,35 , and its inhibition in our data by NAS suggests that MT1 may be responsible for limiting GC proliferation and growth, and at the same time preventing early luteinization at the antral follicular stage through activation of the Akt pathway.…”
Section: Effects Of Mt1 Receptor Activation or Inhibition On Human Gc...supporting
confidence: 74%
“…The list of upstream regulators identified in response to the MT1 agonist N-acetyl serotonin (NAS) used in combination with melatonin (10 −9 M) is available in Supplemental table 7. Microfibrillar-Associated Protein 5 (MFAP5), which is downstream of Akt, downregulates inflammation and controls cell proliferation and progression, had a tendency to be inhibited [31][32][33] . Another factor downstream of Akt, PDZ Domain Containing 1 (PDZK1), also known as Na + /H + Exchanger Regulator Factor-3 (NHERF3) was identified as an upstream regulator.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia, a frequent condition in HNSCC, has been reported to be a critical component of malignant behavior and treatment resistance [ 42 ]. Xu et al demonstrated that MFAP5 could boost EMT process by activation of AKT under hypoxia status [ 43 ]. After hypoxia treatment in HNSCC cell lines, the expression of SRGN was increased by secretion of cancer-associated fibroblasts, which in turn stimulates tumor exacerbation via Wnt/ β -catenin axis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo analysis showed that overexpression of MFAP5 could promote tumor lung metastasis. Experiments show that MFAP5 may promote this process by activating epithelial mesenchymal transformation (EMT) through Akt pathway [ 7 ]. In addition, studies have found that hypoxia-induced ZEB1 can promote the progression of cervical cancer through CCL8-dependent recruitment of tumor-associated macrophages [ 8 ].…”
Section: Introductionmentioning
confidence: 99%